Multidimensional Interests in Horizontal Intergovernmental Coordination: The Case of the German Bundesrat. Issue 2 (21st August 2017) - Hegele, Yvonne
Abstract: In the German Bundesrat, an arena of horizontal intergovernmental relations, sixteen Länder governments composed of approximately 170 governmental departments coordinate and negotiate their positions on federal motions. This article analyzes the coordination process and argues that the interests that the actors pursue, as well as the coordination strategies stemming from these interests, are less clear-cut than commonly assumed. Based on a novel network dataset collected by the author, evidence is found for sectoral, political party, and territorial coordination strategies. The main findings are first, that political party coordination in Germany is more frequent than territorial coordination but performs a structuring instead of a substantial function during the coordination process. Second, sectoral coordination mainly takes place at an early stage of the coordination process and is able to solve a bulk of coordination problems by drawing on expert knowledge.